1995
DOI: 10.1007/bf00011793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term application of animal manure on physical properties of three soils

Abstract: Surface soil samples to 15 cm depth were taken from replicated plots in an ongoing long-term field experiment involving application of animal manure on three soils in Virginia. The sampled plots had received either no manure or the equivalent of 289,000 kg ha-1 of manure as dry weight. The manure was applied annually at the beginning of each spring for 15 years from 1978 through 1992. The plots were cropped similarly since 1978. Soil textures were a fine sandy loam at Holland in the Atlantic Coastal Plain regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
73
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 23 publications
3
73
0
2
Order By: Relevance
“…Maintaining adequate amount of SOM is particularly important for sustaining the productivity of an agro-ecosystem (Lal et al, 1999;Carter, 2002;Ding et al, 2012). Numerous studies have found strong correlations among soil structure, soil aggregate stability and SOM content (Darwish et al, 1995;Haynes and Naidu, 1998). For instance, some studies have shown that increase in SOM improves soil's aggregation, total porosity, hydraulic conductivity, waterholding capacity, resistance to water and wind erosion, and lowers bulk density and the degree of compaction (Celik et al, 2004;Leroy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining adequate amount of SOM is particularly important for sustaining the productivity of an agro-ecosystem (Lal et al, 1999;Carter, 2002;Ding et al, 2012). Numerous studies have found strong correlations among soil structure, soil aggregate stability and SOM content (Darwish et al, 1995;Haynes and Naidu, 1998). For instance, some studies have shown that increase in SOM improves soil's aggregation, total porosity, hydraulic conductivity, waterholding capacity, resistance to water and wind erosion, and lowers bulk density and the degree of compaction (Celik et al, 2004;Leroy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, sufficiently high soil organic carbon levels have to be maintained as they may affect crop yield indirectly by modifying soil physical and chemical properties, offering an improved root environment (Darwish et al, 1995;Stratton et al, 1995;D'Hose et al, 2014). Krey et al (2013) observed a similar or even stronger impact of organic fertilizers applied every third year on plant traits and P availability, compared to the annual application of inorganic P fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Organically managed soils typically differ substantively in fertility as well as a number of soil quality properties when compared to conventionally managed soils [6][7][8][9][10][11] . Organic farming systems have been found to have a greater soil organic matter than the conventional agricultural systems 12,13) , and it has a profound impact on soil quality 7,8,[14][15][16][17] . Organic matter encourages granulation, increases water storage, nutrient supply, and soil organism activity, and improves soil fertility and productivity.…”
Section: Introductionmentioning
confidence: 99%